2012
DOI: 10.1016/j.rbmo.2012.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of transdermal testosterone in poor responders undergoing IVF: systematic review and meta-analysis

Abstract: A systematic review and meta-analysis was performed to evaluate the effect of transdermal testosterone preceding ovarian stimulation in women with poor ovarian response undergoing IVF. Studies comparing pretreatment with transdermal testosterone versus standard ovarian stimulation among poor responders were included. The main outcome assessed was live birth. Three trials were included (113 women in the testosterone group, 112 in the control group). Testosterone-treated women achieved significantly higher live … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 33 publications
1
39
1
2
Order By: Relevance
“…In vitro data indicate that human granulosa cells possess sulfates activity, and that DHEAS can be used as a substrate for both estrogen and androstenedione synthesis [13,14]. Androgens can augment FSH receptor expression in granulosa cells and are thought to promote follicular growth and estrogen biosynthesis by amplifying the effects of FSH in rhesus monkeys [15]. Studies on murine models of conditional granulosa cell and oocyte-specific deletion of the androgen receptor found positive correlations between androgen receptor and FSH receptor expression, suggesting that androgens may prevent preantral follicle growth and atresia [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro data indicate that human granulosa cells possess sulfates activity, and that DHEAS can be used as a substrate for both estrogen and androstenedione synthesis [13,14]. Androgens can augment FSH receptor expression in granulosa cells and are thought to promote follicular growth and estrogen biosynthesis by amplifying the effects of FSH in rhesus monkeys [15]. Studies on murine models of conditional granulosa cell and oocyte-specific deletion of the androgen receptor found positive correlations between androgen receptor and FSH receptor expression, suggesting that androgens may prevent preantral follicle growth and atresia [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Androgens can augment FSH receptor expression in granulosa cells and are thought to promote follicular growth and estrogen biosynthesis by amplifying the effects of FSH in rhesus monkeys [15]. Studies on murine models of conditional granulosa cell and oocyte-specific deletion of the androgen receptor found positive correlations between androgen receptor and FSH receptor expression, suggesting that androgens may prevent preantral follicle growth and atresia [16][17][18][19][20]. Similarly, it has recently been shown that androgen receptor mRNA and androgen levels in follicular fluid correlate with FSH receptor mRNA expression in human granulosa cells from small antral follicles [21].…”
Section: Discussionmentioning
confidence: 99%
“…However, differences observed in clinical pregnancy per embryo transferred were not statistically significant (RR 1.72, 95% CI 0.91 to 3.26). Authors did not observe any difference regarding number and quality of the oocytes retrieved [19]. …”
mentioning
confidence: 85%
“…Different RCTs report a beneficial effect of TT pre-treatment [16,17] and the meta-analysis from Bosdou et al [18] analyzing both trials conducted by Massin et al [16] and Kim et al [17] reported that pretreatment with transdermal testosterone was associated with an increase in clinical pregnancy (risk difference (RD): +15%, 95% confidence interval (CI): +3 to +26%) and live birth rates (RD: +11%, 95% CI: +0.3 to +22%) in poor responders undergoing ovarian stimulation for IVF. A second meta-analysis conducted by Gonzalez-Comadran et al [19] also reported that testosterone-treated women achieved a significantly higher live birth rate (risk ratio, RR, 1.91, 95% CI 1.01 to 3.63), clinical pregnancy rate (RR 2.07, 95% CI 1.13 to 3.78) and required significantly lower doses of FSH (RR -461.96, 95% CI -611.82 to -312.09). However, differences observed in clinical pregnancy per embryo transferred were not statistically significant (RR 1.72, 95% CI 0.91 to 3.26).…”
Section: Testosterone (Tt)mentioning
confidence: 99%
“…Наиболее хорошие результаты получены при использовании тестостерона в виде геля по 12,5-25 мг в течение 15-20 дней до вступления в программу или с 21-го дня преды-дущего цикла до момента назначения ГТ. Механизм положительного эффекта андрогенного прайминга у таких пациенток авторы связывают со способностью андрогенов активизировать ранний рекрутинг фоллику-лов в созревающую когорту, увеличить экспрессию рецепторов к ФСГ на клетках гранулезы малых антраль-ных фолликулов и поддерживать адекватную чувстви-тельность ФСГ-рецепторов на всех гормонально зависи-мых этапах фолликулогенеза [24,25].…”
Section: рис 3)unclassified